3-Dimensional shear wave elastography of breast lesions: Added value of color patterns with emphasis on crater sign of coronal plane. Issue 39 (September 2016) - Chen, Ya-ling; Chang, Cai; Zeng, Wei; Wang, Fen; Chen, Jia-jian; Qu, Ning
Abstract : Abstract: Color patterns of 3-dimensional (3D) shear wave elastography (SWE) is a promising method in differentiating tumoral nodules recently. This study was to evaluate the diagnostic accuracy of color patterns of 3D SWE in breast lesions, with special emphasis on coronal planes. A total of 198 consecutive women with 198 breast lesions (125 malignant and 73 benign) were included, who underwent conventional ultrasound (US), 3D B-mode, and 3D SWE before surgical excision. SWE color patterns of Views A (transverse), T (sagittal), and C (coronal) were determined. Sensitivity, specificity, and the area under the receiver operating characteristic curve (AUC) were calculated. Distribution of SWE color patterns was significantly different between malignant and benign lesions ( P = 0.001). In malignant lesions, "Stiff Rim" was significantly more frequent in View C (crater sign, 60.8%) than in View A (51.2%, P = 0.013) and View T (54.1%, P = 0.035). AUC for combination of "Crater Sign" and conventional US was significantly higher than View A (0.929 vs 0.902, P = 0.004) and View T (0.929 vs 0.907, P = 0.009), and specificity significantly increased (90.4% vs 78.1%, P = 0.013) without significant change in sensitivity (85.6% vs 88.0%, P = 0.664) as compared with conventional US. In conclusion, combination of conventional US with 3D SWE color patterns significantly increased diagnostic accuracy, with "Crater Sign" in coronal plane of the highest value.